Crosstalk between microbiota, pathogens and the innate immune responses - Günther, Claudia; Josenhans, Christine; Wehkamp, Jan (International Journal of Medical Microbiology, 2016)
Research in the last decade has convincingly demonstrated that the microbiota is crucial in order to prime and orchestrate innate and adaptive immune responses of their host and influence barrier function as well as multiple developmental and metabolic parameters of the host. Reciprocally, host reactions and immune responses instruct the composition of the microbiota. This review summarizes recent evidence from experimental and human studies which supports these arms of mutual relationship and crosstalk between host and resident microbiota, with a focus on innate immune responses in the gut, the role of cell death pathways and antimicrobial peptides. We also provide some recent examples on how dysbiosis and pathogens can act in concert to promote intestinal infection, inflammatory pathologies and cancer. The future perspectives of these combined research efforts include the discovery of protective species within the microbiota and specific traits and factors of microbes that weaken or enforce host intestinal homeostasis.
EVALuna2:2213